An Enhance Performance of State Court Office Employees Based on Competency, Motivation and Communication - Muhammad Arief Pohan; Hasrul Azwar Hasibuan; M. Isa Indrawan (Budapest International Research and Critics University, 2022)
This research was conducted to explain the partial or simultaneous influence of competence, motivation, and communication variables on the performance of the Medan District Court's employees. The total population used was 65 respondents who worked at the Medan District Court Office which was taken using a questionnaire that was used as a data collection method in this study. Where using multiple linear regression analysis and the results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the variables of competence, motivation, and communication on the performance of Medan District Court employees.